Metastamir - the field of metastasis-regulatory microRNA is spreading - Hurst, Douglas R. (2009)
Despite advancements in knowledge from over a century of metastasis research, the genetic programs and molecular mechanisms required for cancer metastasis are still incompletely understood. Genes that specifically regulate the process of metastasis are useful tools to elucidate molecular mechanisms and may become markers and/or targets for anti-metastatic therapy. Recently, several non-coding regulatory RNA genes, microRNA (miRNA), were identified that play roles in various steps of metastasis, some without obvious roles in tumorigenesis. Understanding how these metastasis-associated miRNA, which we term metastamir, are involved in metastasis will help identify possible biomarkers or targets for the most lethal attribute of cancer - metastasis.